EVALUATING GROWTH AND NUTRIENT COMPOSITION OF AFRICAN CATFISH UNDER DIFFERENT SALINITIES - Owis, Muhammad; Al Sulivany, Basim. S. A.; Fazal, Rana M.; Abdellatif, Manar (Science Journal of University of Zakho, 2024)
An investigation was carried out to explore the effect of salinity on the growth and flesh quality of African catfish (Clarias gariepinus), a significant species in global aquaculture. Fifty juvenile catfish of weight 24.25±0.4g were collected from the Chenab River in Pakistan and acclimatized in controlled aquaculture conditions at different salinity levels NaCl (T1; 0, T2; 2, T3; 4; T4; 6, and T5; 8 ppt) over 60 days. Growth performance indicators, including final weights, weight gain, growth rate, and feed conversion ratio (FCR), were measured. The statistical result indicated that the fish in lower salinity environments (0-2 ppt) exhibited significant (p < 0.05) final weights, weight gain, and growth rates, with performance declining significantly as salinity increased. The best FCR 1.2±0.01 was indicated at 0 ppt, while the highest salinity (8 ppt) was revealed in the FCR 1.7±0.04. Proximate composition analysis indicated that crude protein and moisture content elevated with salinity while crude fat and ash content decreased. These results suggest that C. gariepinus thrives in slightly brackish conditions, with optimal growth at low salinity levels. However, higher salinities adversely impact physiological health and growth performance.